Updating of working memory in ecstasy polydrug users: Findings from fNIRS. (19th June 2017) - Montgomery, Catharine; Fisk, John E.; Roberts, Carl A.
Abstract: Aims/Objectives: Cognitive deficits are now well documented in ecstasy (MDMA) users with type and relative demand of task emerging as important factors. The updating component of executive processes appears to be particularly affected. The study reported here used functional near infrared spectroscopy imaging to investigate changes in cortical haemodynamics during memory updating. Method: Twenty ecstasy users and 20 non‐users completed verbal and spatial memory updating tasks and brain blood oxygenation and deoxygenation change was measured using functional near infrared spectroscopy. Results: There was no interaction between group and difficulty on the updating tasks, though there was a significant main effect of difficulty on both tasks. The effects of group approached significance on the verbal updating task. There were significant differences in blood oxygenation and deoxygenation change at optodes centred over the right and left dorsolateral prefrontal cortex, with ecstasy users showing greater blood oxygenation than the other groups. Discussion: The lack of a behavioural difference on both tasks but presence of blood oxygenation and deoxygenation changes in letter updating provides support for the notion that ecstasy‐polydrug users are investing more effort to achieve the same behavioural output. Total lifetime dose was high, and recency of use was significantly related to most changes, suggesting that heavy and recent use may be particularly detrimental.